2016
DOI: 10.3390/bs6030017
|View full text |Cite|
|
Sign up to set email alerts
|

Is Internet Pornography Causing Sexual Dysfunctions? A Review with Clinical Reports

Abstract: Traditional factors that once explained men’s sexual difficulties appear insufficient to account for the sharp rise in erectile dysfunction, delayed ejaculation, decreased sexual satisfaction, and diminished libido during partnered sex in men under 40. This review (1) considers data from multiple domains, e.g., clinical, biological (addiction/urology), psychological (sexual conditioning), sociological; and (2) presents a series of clinical reports, all with the aim of proposing a possible direction for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 181 publications
3
93
1
5
Order By: Relevance
“…Many report increased desire to be in a relationship, more pleasure from intimacy, and a very different, more human, perception of potential mates. It is likely that these benefits, like the initial symptoms, are the result of neuroplastic changes (Park et al, 2016). Some 4,000 recovery self-reports gathered from online recovery forums can be viewed at www.yourbrainonporn.com (Your Brain on Porn, 2016).…”
Section: The Online Porn Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many report increased desire to be in a relationship, more pleasure from intimacy, and a very different, more human, perception of potential mates. It is likely that these benefits, like the initial symptoms, are the result of neuroplastic changes (Park et al, 2016). Some 4,000 recovery self-reports gathered from online recovery forums can be viewed at www.yourbrainonporn.com (Your Brain on Porn, 2016).…”
Section: The Online Porn Experimentsmentioning
confidence: 99%
“…However, since 2010, six studies have found ED rates of 27%-33% in young men, a 1000% increase in the last 15 years (Park et al, 2016).…”
Section: How Many Pornography Users Are Adversely Affected?mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, levels of impotence among young men have been 2% to 5% (Park et al, 2016). A range of recent studies are finding that 27% to 33% of young men age 18-40 years are having erectile difficulties and low libido rates with a real partner (Bronner & Ben-Zion, 2014;Klucken, Wehrum-Osinsky, Schweckendiek, Kruse, & Stark, 2016;Kühn & Gallinat, 2014;Mialon, Berchtold, Michaud, Gmel, & Suris, 2012;Pizzol, Bertoldo, & Foresta, 2015;Sutton, Stratton, Pytyck, Kolla, & Cantor, 2015), though not with internet pornography (Landripet & Štulhofer, 2015).…”
Section: Harm Minimization -Reducing Demand For Legal Pornographymentioning
confidence: 99%
“…Essentially, they have conditioned their brains to respond to images on a screen and not to real partners. For most young men, this problem can be treated by discontinuing their use of pornography (Pacha, 2016;Park et al, 2016;Porto 2016).…”
Section: Harm Minimization -Reducing Demand For Legal Pornographymentioning
confidence: 99%